2012
DOI: 10.5424/sjar/2012104-2899
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a UV-absorbing greenhouse covering film on tomato yield and quality

Abstract: The effect of blocking the ultraviolet (UV) solar radiation using a UV-absorbing low density polyethylene (PE) film on tomato crop yield and fruit quality was evaluated in a two-year study in two arched roof greenhouses located in Central Greece. The UV-A and UV-B radiation transmission values of the greenhouse covered by the UVabsorbing PE film during the first year were 0.4% and 1.2%, respectively and increased to 0.8% and 1.3% in the 2 nd year, while the respective values in the greenhouse covered by a trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…reported a monthly variation in sugar levels of tomato fruit grown in greenhouses with different cooling systems and further concluded that sugar content was not affected by greenhouse type and climate conditions. In addition, Papaioannou et al . did not find a significant effect of PE cover materials on TSS content of tomato fruit.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…reported a monthly variation in sugar levels of tomato fruit grown in greenhouses with different cooling systems and further concluded that sugar content was not affected by greenhouse type and climate conditions. In addition, Papaioannou et al . did not find a significant effect of PE cover materials on TSS content of tomato fruit.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, Farneti et al 36 reported a monthly variation in sugar levels of tomato fruit grown in greenhouses with different cooling systems and further concluded that sugar content was not affected by greenhouse type and climate conditions. In addition, Papaioannou et al 17 did not find a significant effect of PE cover materials on TSS content of tomato fruit. In addition, Toor et al 37 detected a great variation in TSS content during the growing season for three greenhouse-grown tomato genotypes suggesting a genotype-dependent effect.…”
Section: Chemical Compositionmentioning
confidence: 90%
See 1 more Smart Citation
“…A different response to UV-B depletion between the two genotypes was actually not unexpected. Previous studies indicated that the influence of low UV-B radiation levels on ascorbic acid and lycopene levels (Giuntini et al, 2005) and content of total soluble solids in fruits (Krizek et al, 2006) depends on tomato genotype and that the results obtained may be valid only for the tomato cultivar studied (Papaioannou et al, 2012). A genotype-dependence was observed also in two tomato hybrids characterised by a high (DRW 5981) or a low lycopene (Esperanza) content, with DRW 5981 undergoing a decrease and Esperanza an increase in HCAs content in peel following UV-B shielding (Giuntini et al, 2008).…”
Section: Effect Of Uv-b Depletion In Peel Of Wild Type and Hp-1mentioning
confidence: 99%
“…Anthocyanins synthesis can be affected by many different factors, among them, temperature, light intensity, nutrition, and irrigation [5]. Some of these factors are strongly modified by the use of covering materials in protected cultivation (either under greenhouse or net), thus aggravating poor color development in the skin of the fruit [6]. Cultural practices common in table grape, such as leaf removal and shoot and cluster thinning, seek enhancing berry appearance [7,8], but commonly are not enough to resolve color deficits.…”
Section: Introductionmentioning
confidence: 99%